Design and Implementation of Marketing Strategy and Financial Report Based on Integrated Technology Teaching Factory (TEFA) in the Development of SMEs Based on Environmentally Friendly Products "Manado Ecocrafts" - Don Kabo; Putong, Ivonne Helena; Joroh, Adelaida; Kolondam, Arifmanuel (Indonesian Journal of Society Development, 2024)
This study aims to design and implement a marketing strategy and a technology-based financial reporting system integrated with the Teaching Factory (TEFA) concept to support the development of environmentally friendly micro-enterprises, especially in Manado Ecocrafts. The INOVOKASI program includes the implementation of Appropriate Technology, marketing digitalization training, and a modern financial management system to improve the efficiency, productivity, and competitiveness of micro-enterprises in local and global markets. Manado Ecocrafts, as a business partner, faces challenges in managing raw materials, limited production technology, and market access. Through this program, solutions are implemented such as the use of digital technology for financial recording, e-commerce-based marketing strategies, and optimizing product distribution. As a result, there is an increase in production efficiency of up to 50%, an increase in turnover of up to 10% in the first six months, and market expansion through digital platforms.This program provides economic sustainability benefits for partners and local communities through increasing human resource capacity, empowering communities, and contributing to reducing environmental waste. In conclusion, the strategies implemented have succeeded in supporting the growth of micro-enterprises and building innovative and sustainable business models.